Just Friends? Queering Male–Male Amity in Jean de Beaubreuil's Regulus (1582). (1st October 2020) - Meere, Michael
ABSTRACT: This article proposes a queer (re)reading of Jean de Beaubreuil's Roman tragedy Regulus ([1582] 1999). The study begins with an exploration of the author's trip to Rome and his visit with Marc-Antoine Muret, a renowned humanist who fled France in 1554 due to charges of heresy and sodomy. It then reads queerly two key passages from the play to suggest that the tragedy's most strikingly queer elements include the intimate friendship formed between the main dramatis personae (Atilie and Manlie), their ritual of unity before battle that resembles a clandestine marriage ceremony, the mythological and historical references evoked during this ritual, and the replacement of Regulus's legendary wife and children with Manlie. The article concludes with an analysis of the tensions between the hero's public persona (Regulus) and private identity (Atilie), which invites the reader to reconsider the modalities of male–male amity in sixteenth-century France.